Trestenshult och den tidiga småländska glashanteringen - Hansson, Martin (Hikuin, 2010)
Trestenshult and the early glassworks in Småland By Martin Hansson This article discusses and presents the glasswork of Trestenshult in southern Småland. The site was excavated in 1932 and in 1974, but the material have never been properly analysed. The glasswork existed a couple of years around 1630 and was founded by Karl Karlsson Gyllenhielm, bastard son to duke Karl, the later king Karl IX of Sweden. As many other glassworks of this period, Trestenshult was connected to the higher aristocracy and the royal family. The production of Trestenshult was varied, and medical glasses, bowls, drinking glasses as well as window glass were produced. The production was partly intended for Gyllenhielms own needs, partly for sale. The glasswork is fairly well preserved and situated in a forest close to a minor stream. Remains of the glass work with the oven, a dam and mill can be found on the site. The article summarizes the results of the previous excavations at Trestenshult, which is seen as a suitable place for further research, especially regarding spatial analysises of how a late Renaissance glass work was constructed. Some outlines for future research is given.